(untitled) (European Journal of Formal Sciences and Engineering, 2023)
One of the major concerns in the seismic retrofitting of masonry walls is that of increasing the ultimate load for out-of-plane forces. In multi-story buildings, these forces may originate from the hammering actions of floors, when the earthquake direction is orthogonal to the wall. A possibility for counteracting the out-of-plane displacements is retaining the wall by building some buttresses, that is, some beams lean against the wall and disposed vertically. Another possibility is to make the buttress in the thickness of the wall. In this second case, we must cut the wall for its entire height, realize the buttress, and restore the masonry wall around it. In both cases, the interventions are highly invasive. The first intervention also leads to increments of mass that enhance the attraction of seismic forces. The aim of this paper is to find a less invasive and lighter alternative for realizing buttresses. We proposed to use FRP strips and steel ribbons in a combined fashion, so as to realize an ideal vertical I-beam embedded into the wall, without requiring to cut the masonry. We also provided some experimental results for verifying the effectiveness of the model.